Longitudinal changes in epigenetic age in youth with perinatally acquired HIV and youth who are perinatally HIV-exposed uninfected. (1st April 2021) - Shiau, Stephanie; Brummel, Sean S.; Kennedy, Elizabeth M.; Hermetz, Karen; Spector, Stephen A.; Williams, Paige L.; Kacanek, Deborah; Smith, Renee; Drury, Stacy S.; Agwu, Allison; Ellis, Angela; Patel, Kunjal; et al.
Abstract : Objectives: To quantify the rate of change in epigenetic age compared with chronological age over time in youth with perinatally acquired HIV (YPHIV) and youth who are perinatally HIV-exposed uninfected (YPHEU). Design: Longitudinal study of 32 YPHIV and 8 YPHEU with blood samples collected at two time points at least 3 years apart. Methods: DNA methylation was measured using the Illumina MethylationEPIC array and epigenetic age was calculated using the Horvath method. Linear mixed effects models were fit to estimate the average change in epigenetic age for a 1-year change in chronological age separately for YPHIV and YPHEU. Results: Median age was 10.9 and 16.8 years at time 1 and 2, respectively. Groups were balanced by sex (51% male) and race (67% black). Epigenetic age increased by 1.23 years (95% CI 1.03--1.43) for YPHIV and 0.95 years (95% CI 0.74--1.17) for YPHEU per year increase in chronological age. Among YPHIV, in a model with chronological age, a higher area under the curve (AUC) viral load was associated with an increase in epigenetic age over time [2.19 years per log10  copies/ml, (95% CI 0.65--3.74)], whereas a higher time-averaged AUC CD4 + T-cell count was associated with a decrease in epigenetic age over time [−0.34 years per 100 cells/μl, (95% CI −0.63 to −0.06)] in YPHIV. Conclusion: We observed an increase in the rate of epigenetic aging over time in YPHIV, but not in YPHEU. In YPHIV, higher viral load and lower CD4 + T-cell count were associated with accelerated epigenetic aging, emphasizing the importance of early and sustained suppressive treatment for YPHIV, who will receive lifelong ART.